Factors Affecting Tissue Culture-Induced Variations - Sánchez-Romero, Carolina (Springer Nature, 2024)
In vitro culture can induce somaclonal variation, giving rise to the appearance of alterations in the cultured cells and tissues, as well as in the regenerated plants and their progenies. A wide range of alterations can emerge as a consequence of somaclonal variation, which can be detected at different levels, such as phenotypic, cytogenetic, biochemical or molecular. Both nature and frequency of changes are uncontrolled due to the unpredictable nature of somaclonal variation. Thus, somaclonal variation is considered an important drawback intrinsically associated to the use of in vitro culture techniques and, in fact, it constitutes a very important problem in culture systems in which true-to-typeness is expected. Nevertheless, it can also be used as a source of genetic variability which can be exploited in plant improvement. Comprehensive knowledge of the effect of different factors affecting somaclonal variation, such as the genotype, explant source, culture conditions, culture age or the in vitro culture method, can help to design strategies in order to reduce or promote somaclonal variation, depending on the objectives that have determined the use of in vitro culture.
Somaclonal Variation: Basic and Practical Aspects
Springer permite el depósito de la versión aceptada del capítulo de libro. https://www.springernature.com/gp/open-science/policies/book-policies
Keywords: Biodiversidad - Aspectos genéticos; Somaclonal variation